Abundance and diversity of microbial arsenic biotransformation genes in the sludge of full-scale anaerobic digesters from a municipal wastewater treatment plant. (May 2020) - Zhai, Weiwei; Qin, Tianyue; Li, Liguan; Guo, Ting; Yin, Xiaole; Khan, Muhammad Imran; Hashmi, Muhammad Zaffar; Liu, Xingmei; Tang, Xianjin; Xu, Jianming
Highlights: The species and biotransformation genes of As in the sludge during anaerobic digestion was explored. As(III) and As(V) were the predominant forms in the influent sludge, whereas MMA increased significantly after digestion. As biotransformation genes were highly abundant in the sludge, and arsM gene was the predominant. The abundance and diversity of the arsM -like sequences increased significantly after digestion. Co-occurrence network analysis indicated a strong correlation between the microbial communities and As. Abstract: Arsenic (As) is a potential contaminant in sewage sludge that may affect waste treatment and limit the use of these waste materials as soil amendments. Anaerobic digestion (AD) is an important and effective process for the treatment of sewage sludge and the chemical speciation of As is particularly important in sludge AD. However, the biotransformation genes of As in sludge during AD has not been fully explored. In this study, the influent and effluent sludge of anaerobic digester in a wastewater treatment plant (WWTP) was collected to investigate the species transformations of As, the abundance and diversity of As biotransformation genes was explored by real-time PCR (qPCR) and metagenomic sequencing, separately. The results showed that arsenite [As(III)] and arsenate [As(V)] were predominant in the influent sludge, whereas the relative abundance of monomethylarsenic acid (MMA) increased by 25.7% after digestion. As biotransformation genes were highly abundant, and the As(III) S-adenosylmethionine methyltransferase ( arsM ) gene was the predominant which significantly increased after AD by qPCR analysis. Metagenomic analysis indicated that the diversity of the arsM -like sequences also increased significantly after AD. Most of the arsM -like sequences in all the influent and effluent sludge samples were related to Bacteroidetes and Alphaproteobacteria. Furthermore, co-occurrence network analysis indicated a strong correlation between the microbial communities and As. This study provides a direct and reliable reference on As biotransformation genes and microbial community in the AD of sludge.